Construction of a local location program on the basis of “decision tree” - Przemysław Duer; Stanisław Duer; Paweł Wrzesień (Biuletyn Wojskowej Akademii Technicznej, 2019)
The article presents the problems of building a damage location program in a technical facility based on the theory of the “decision tree”. The basis in such a decision-making process is the functional and diagnostic analysis of the tested technical device. The result of this analysis process is a set of basic (functional) elements with a set of weighting factors assigned to them. An algorithm of fault location is developed in the theory of the “decision tree” in the process of locating faults in the tested vehicle power supply system. Keywords: technical diagnostics, diagnostic reasoning, artificial intelligence.